Evaluation of Antimicrobial Activity of Deodar Substrate and Hemp Seeds against Fungal Pathogens Infecting Apple - Kumar, Arunesh; Gupta, Meenu; Sharma, Satish Kumar; Kumar, Surender; Bhardwaj, Chidembra; Verma, Ranjeet Singh; Ankita; Kumar, Gokul (International Journal of Economic Plants, 2025)
The experiment was conducted during May–June, 2024 at Dr Y S Parmar University of Horticulture and Foresrty, Nauni, Solan (H.P.) to study the antimicrobial activity of deodar substrate and hemp seeds against major soil-borne pathogens of apple. An in vitro investigation was performed to assess the effects of deodar sawdust (Cedrus deodara) and hempseed (Cannabis sativa) on the mycelial growth of three soil-borne (Fusarium oxysporum, Sclerotium rolfsii and Dematophora necatrix) and one foliar (Colletotichum spp) pathogen in apple trees, aiming to find sustainable alternatives to chemical fungicides. The most significant inhibitory impact of this organic amendment was seen on Fusarium oxysporum, showing 74.44% reduction in growth with 23 mm mycelial development one week post inoculation, followed by Dematophora necatrix, which demonstrated 70.00% inhibition. Conversely, the least inhibition was noted for Sclerotium rolfsii (16.67%) which had maximum mycelial growth (75.00 mm). Combining deodar sawdust and hempseed could have synergistic effect and antagonistic effects to certain soil-borne pathogens in apple orchards, while complementary enhancement of soil health and resilience, however, it is important to conduct field trials for tailored recommendations.